Investigating Perceptions of Online Paraphrasing Tools among English-Majored Students at Sai Gon University in Learning Academic Writing - Cao, Hoang Minh Nguyet; Lam, Minh Phuong Uyen (IPI Garut Press, 2025)
Abstract English academic writing, especially scientific reports, is difficult due to many problems. In particular, many researchers found that a large number of students are still unable to effectively paraphrase English texts, as shown by the fact that the majority of the sources are almost exactly repeated in the students' work, leading to unintentional plagiarism. To address the lack of paraphrasing skill, Artificial Intelligence (AI) can provide students with great assistance. Therefore, this study aims to investigate Sai Gon University students' perceptions towards online paraphrasing tools and recommend some ways to avoid plagiarism in learning academic writing. The data from 100 random English-majored seniors were collected through questionnaires and interviews. The findings revealed positive perceptions of students towards the utilization of online paraphrasing tools in learning academic writing. Most of them found these tools beneficial for their improvement in paraphrasing skill. Based on the data collected, the study recommends some useful and appropriate ways to avoid plagiarism by using AI tools in their writing.